Does Financial Inclusion Induce Financial Stability? Evidence from Cross-country Analysis - Md. Nur Alam Siddik; Sajal Kabiraj (Australasian Accounting, Business and Finance Journal, 2018)
In recent times, financial inclusion and financial stability issue have become a priority on policy agendas across the world. However, there is relative dearth of empirical studies addressing and establishing the link between the same. This study fills this gap. Using panel data of 2001-2013, this study empirically investigated whether financial inclusion contributes to country’s financial stability, measured by Z-score. Robust results from GMM dynamic panel data estimator show that financial inclusion variables as measured by number of SME borrowers to total borrowers and ratio of outstanding SME loans to total loans have significant positive contributions to financial stability. Findings also indicate that GDP per capita, liquidity, proportion of private credit to GDP are positively and proportion of domestic credit provided to private sector and financial crisis are negatively associated with financial stability. Empirical findings of this study is of greater significance to the policymakers as it will invoke the attention of governments and policymakers to undertake such policies to accelerate financial inclusion of their countries which in turn will lead to country’s greater financial stability. This study also contributes to empirical literatures of the issue of financial inclusion and financial stability by reconfirming (or otherwise) findings of previous studies.
Keywords: Financial stability; financial inclusion; financial openness; GMM dynamic panel estimator; robustness.